2018
DOI: 10.1111/ejn.14187
|View full text |Cite
|
Sign up to set email alerts
|

The role of the cerebellum in drug‐cue associative memory: functional interactions with the medial prefrontal cortex

Abstract: Drug‐induced Pavlovian memories are thought to be crucial for drug addiction because they guide behaviour towards environments with drug availability. Drug‐related memory depends on persistent changes in dopamine‐glutamate interactions in the medial prefrontal cortex (mPFC), basolateral amygdala, nucleus accumbens core and hippocampus. Recent evidence from our laboratory indicated that the cerebellum is also a relevant node for drug‐cue associations. In the present study, we tested the role that specific regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 72 publications
2
34
0
Order By: Relevance
“…Recent findings from our laboratory indicate that the cerebellum can control learning-related activity (Gil-Miravet et al, 2018) and plasticity in the infralimbic cortex (unpublished results). Neurotoxic lesion of the posterior cerebellar cortex performed before conditioning increased cFos expression and mechanisms for synaptic stabilization in the infralimbic cortex.…”
Section: Cerebellar Underpinnings Of Compulsivitymentioning
confidence: 62%
“…Recent findings from our laboratory indicate that the cerebellum can control learning-related activity (Gil-Miravet et al, 2018) and plasticity in the infralimbic cortex (unpublished results). Neurotoxic lesion of the posterior cerebellar cortex performed before conditioning increased cFos expression and mechanisms for synaptic stabilization in the infralimbic cortex.…”
Section: Cerebellar Underpinnings Of Compulsivitymentioning
confidence: 62%
“…Infusions were released through a removable stainless-steel injector (length, Figure 4A). More detailed information can be found in Gil-Miravet et al 37…”
Section: Brain Infusions and Stereotactic Surgerymentioning
confidence: 99%
“…37 Moreover, simultaneous IL-cerebellar deactivation prevented the effect of either of the separate manipulations. 37 These results were in agreement with findings reporting that the IL cortex is required for the suppression of cocaine-seeking response and expression of extinction memory. 38,39 Overall, our findings suggested that both the cerebellum and IL cortex might act together in regulating the establishment of drug-cue Pavlovian associations.…”
mentioning
confidence: 97%
“…Cerebellar-mediated dopamine pathways have previously been shown to exhibit plasticity and compensatory changes in the neural circuitry of rodent models of autism, providing a foundation for the cerebellum to develop unique connections between cerebral hemispheres [67]. Some hypothesize that the corpus callosum enables hemispheric specializations, allowing one hemisphere to reconfigure circuits and adapt to certain environmental changes while the other hemisphere preserves existing functions [77].…”
Section: Discussionmentioning
confidence: 99%